Multinuclear absolute magnetic resonance thermometry - Silletta, Emilia Victoria (2019)
Non-invasive measurement of absolute temperature is important for proper characterization of various pathologies and for evaluation of thermal dose during interventional procedures. The proton (hydrogen nucleus) magnetic resonance (MR) frequency shift method can be used to map relative temperature changes. However, spatiotemporal variations in the main magnetic field and the lack of local internal frequency reference challenge the determination of absolute temperature. Here, we introduce a multinuclear method for absolute MR thermometry, based on the fact that the hydrogen and sodium nuclei exhibit a unique and distinct characteristic frequency dependence with temperature and with electrolyte concentration. A one-to-one mapping between the precession frequency difference of the two nuclei and absolute temperature is demonstrated. Proof-of-concept experiments were conducted in aqueous solutions with different NaCl concentrations, in agarose gel samples, and in freshly excised ex vivo mouse tissues. One-dimensional chemical shift imaging experiments also demonstrated excellent agreement with infrared measurements.